2017
DOI: 10.1007/s40429-017-0166-7
|View full text |Cite
|
Sign up to set email alerts
|

A Policy Perspective on the Global Use of Smokeless Tobacco

Abstract: BackgroundGlobally, over 300 million people consume diverse smokeless tobacco (ST) products. They are addictive, cause cancer, increased cardiovascular mortality risks and poor pregnancy outcomes.Purpose of ReviewTo identify gaps in implementing key ST demand-reduction measures, focused literature reviews were conducted and findings synthesized according to relevant WHO Framework Convention on Tobacco Control (FCTC) Articles.Recent FindingsThe literature supports implementation of ST demand-reduction measures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…Although initially focused on cigarette smoking, regulation of SLT products has also increased in recent years. Legal decisions aided by the advocacy measures by civil society and non-governmental organizations have allowed to regulate and control the use of tobacco 55 56 57 58 59 . Despite all these measures to restrict the promotion of any form of tobacco products as well as dissemination of knowledge and awareness of adverse impact of tobacco use, nearly 45.3 per cent of women SLT users did not notice health-related warnings on SLT products, much higher than the male counterparts (21.5%) 12 .…”
Section: Marketing Promotion and Regulationmentioning
confidence: 99%
“…Although initially focused on cigarette smoking, regulation of SLT products has also increased in recent years. Legal decisions aided by the advocacy measures by civil society and non-governmental organizations have allowed to regulate and control the use of tobacco 55 56 57 58 59 . Despite all these measures to restrict the promotion of any form of tobacco products as well as dissemination of knowledge and awareness of adverse impact of tobacco use, nearly 45.3 per cent of women SLT users did not notice health-related warnings on SLT products, much higher than the male counterparts (21.5%) 12 .…”
Section: Marketing Promotion and Regulationmentioning
confidence: 99%
“…To identify gaps in implementing key SLT demand-reduction measures, Siddiqi et al confirmed the limited content of the published literature and pointed out the fact that most studies were conducted outside Southeast Asia, the geographical region with the highest SLT prevalence of use 41. They concluded that the literature supports that some SLT demand-reduction measures have been implemented; however, for taxation, labelling and packaging, most administrations have weaker policies for SLT than for cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…The paucity of research and dearth of adequate evidence base on the extent of problem and harmful effects of SLT lead to barriers in effective implementation of SLT control measures by the interested stakeholders 9 . A recent study by Suliankatchi et al 10 reported a shift in the preference of tobacco users from smoking to SLT use in SEAR countries including Bangladesh, India and Nepal.…”
Section: Discussionmentioning
confidence: 99%